Real-World Persistence and Effectiveness of Upadacitinib versus Other Janus Kinase Inhibitors and Tumor Necrosis Factor Inhibitors in Australian Patients with Rheumatoid Arthritis - Peter Youssef; Sabina Ciciriello; Talib Tahir; Joanna Leadbetter; Belinda Butcher; Miriam Calao; Nicole Walsh; Catherine O’Sullivan; Tegan Smith; Geoffrey Littlejohn (Rheumatology and Therapy)
Abstract Introduction This study sought to describe treatment patterns, persistence, and effectiveness of upadacitinib (UPA) alone and compared to other Janus kinase inhibitors (JAKis) or tumor necrosis factor inhibitors (TNFis) in patients with rheumatoid arthritis (RA). Methods This retrospective, non-interventional study used the OPAL dataset, derived from electronic medical records. Patients initiated UPA (N = 2624), other JAKis (baricitinib and tofacitinib [N = 925]), or TNFis (adalimumab, etanercept, certolizumab, golimumab, infliximab [N = 3540]) between May 2020 and March 2023. Median persistence (Kaplan–Meier) and effectiveness (Disease Activity Score 28-joint C-reactive protein, three variables [DAS28CRP{3}]) were evaluated for UPA-treated patients and in three propensity score-matched cohorts: UPA monotherapy versus combination therapy, UPA versus other JAKis, and UPA versus TNFis. Results In patients prescribed UPA, 41.3% were ≥ 65 years old, 33.8% were prescribed as first-line advanced therapy, and 27.2% were prescribed monotherapy. Persistence on UPA was 26.6 months (95% confidence intervals: 24.4, 29.9) and longest in earlier lines of therapy. The DAS28CRP(3) remission rate was 73% at 3 months, with improvements observed across lines of therapy. UPA monotherapy and combination therapy had similar persistence (27.8 [23.5, 33.4] versus 30.4 months [22.1, 35.3], p = 0.84) and effectiveness. UPA showed longer persistence than other JAKis (28.8 [25.6, 32.4] versus 17.2 months [14.9, 19.8], p < 0.001) and TNFis (26.6 [24.9, 30.8] versus 13.3 months [11.5, 14.5], p < 0.001). DAS28CRP(3) remission rates were greater at 3 months for UPA than other JAKis (75.0% versus 61.5%) and TNFis (72.7% versus 59.5%). In unmatched subgroups, compared to cycling between TNFis, switching to UPA from other JAKis or TNFis resulted in longer persistence (JAKi-to-UPA: 25.3 [16.1, not reached]; TNFi-to-UPA: 27.8 [23.2, 35.4]; TNFi-to-TNFi: 9.6 [8.4, 10.7]) and greater DAS28CRP(3) remission rates over 9 months. Conclusions Overall, the breadth and depth of data from this large real-world dataset continue to support a favorable clinical profile of UPA for the treatment of RA and may inform treatment choices in everyday clinical practice.